Penggunaan exambro sebagai evaluasi Pembelajaran PAI - Anisatul Mufidah; Moh. Muslih; Titien Soewastiningsih Soebari (CV Edujavare Publishing, 2024)
The aim of this research is to examine the use of the exambro application as an evaluation of PAI learning at MTs Al-Istiqomah Banyuputih. The method used in this research uses a qualitative descriptive approach, with the type of field research. The research objects were teachers and students of MTs Al-Istiqomah Banyuputih. The research results show that the Exambro application is very effective as a medium for assessing and evaluating PAI learning at MTs Al-Istiqomah Banyuputih. The Exambro application was developed to assist in learning evaluation activities. This application has high security features to prevent cheating in the exam. During the exam, students cannot browse, search on the internet, chat on WhatsApp and anything related to social media, students also cannot open other applications during the exam. Assessments using the Exambro application are more effective than conventional assessments that use paper. Assessments using paper require greater costs, but the quality of the writing is sometimes unclear and blurry. Meanwhile, assessment using the Exambro application is more effective in terms of costs and energy and efficient in terms of time. The weakness of using the Exambro application is that when signal problems occur, this application cannot be used properly